2020
DOI: 10.2139/ssrn.3532373
|View full text |Cite
|
Sign up to set email alerts
|

Does Energy Efficiency Predict Mortgage Performance?

Abstract: We examine a unique micro-level data set on residential mortgages in the United Kingdom. Our analyses suggest that mortgages against energy-efficient properties are less frequently in payment arrears than mortgages against energy-inefficient properties. This result is robust when controlling for other relevant determinants of mortgage default including borrower income and the loan to value ratio of the mortgage. We conclude that energy efficiency is a relevant predictor of mortgage defaults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
1
Order By: Relevance
“…23 Kaza et al (2014), Guin i Korhonen (2018. Vegeu també els informes del European Energy efficient Mortgages Market Implementation Plan (2019).…”
Section: Majories Simples Per a La Renovació D'edificis En Règim De P...unclassified
“…23 Kaza et al (2014), Guin i Korhonen (2018. Vegeu també els informes del European Energy efficient Mortgages Market Implementation Plan (2019).…”
Section: Majories Simples Per a La Renovació D'edificis En Règim De P...unclassified
“…Jurisdictions leading the development and preliminary implementation of more systematic climate stress tests have experience conducting climate-related risk research, stakeholder engagement, scenario analyses, and stress test pilots, as well as issuing complementary supervisory guidance. For example, in advance of the Climate Biennial Exploratory Scenario (CBES), the BOE produced extensive research on climate-related financial risks [ 109 , 144 – 147 ], conducted a survey of industry climate risk practices [ 148 ], issued a supervisory statement on climate risk [ 149 ], and launched a pilot climate stress test for the insurance sector [ 110 , 111 ]. Similarly, in advance of the implementation of climate stress tests [ 117 ], European authorities partnered to conduct climate scenario analyses [ 94 , 95 , 98 ], publish supervisory guidance for climate risk analysis and disclosure [ 150 ], and review bank-led climate stress testing practices as part of alignment with supervisory expectations [ 74 ].…”
Section: Climate Stress Testing Practicesmentioning
confidence: 99%
“…Ref. [51], dealing with the UK market, found that "mortgages against energy-efficient properties are less frequently in payment arrears" even taking into account borrowers' income. Therefore, "the energy efficiency of a property is a relevant predictor of mortgage payment arrears".…”
Section: The Role Of Green Mortgagesmentioning
confidence: 99%